Fast lithium growth and short circuit induced by localized-temperature hotspots in lithium batteries - Yangying Zhu (Nature Portfolio, 2019)
Operation of lithium batteries at high, non-uniform temperatures can lead to safety issues, but the effects of localized high temperatures are difficult to probe. Here the authors use micro-Raman spectroscopy to show that local-temperature hotspots can induce lithium metal growth and trigger circuit shorting.